The Structural Invisibility of Outsiders: The Role of Migrant Labour in the Meat-Processing Industry. (April 2017) - Lever, John; Milbourne, Paul
This article examines the role of migrant workers in meat-processing factories in the UK. Drawing on materials from mixed methods research in a number of case study towns across Wales, we explore the structural and spatial processes that position migrant workers as outsiders. While state policy and immigration controls are often presented as a way of protecting migrant workers from work-based exploitation and ensuring jobs for British workers, our research highlights that the situation 'on the ground' is more complex. We argue that 'self-exploitation' among the migrant workforce is linked to the strategies of employers and the organisation of work, and that hyper-flexible work patterns have reinforced the spatial and social invisibilities of migrant workers in this sector. While this creates problems for migrant workers, we conclude that it is beneficial to supermarkets looking to supply consumers with the regular supply of cheap food to which they have become accustomed.